EFFORTS TO IMPROVE THE EFFECTIVENESS OF LEARNING MODELS (A Case Study Using Faststone in Online Learning at SMK NEGERI 1 Juwiring) - Heni Budianti; Sri Sarjana (PAEDAGOGIA, 2021)
Online learning is learning process to gain knowledge through a set of electronic devices with relevant application programs and connected to internet. Teachers must develop various effective learning models during pandemic. Online learning needs to be done as long as there is no classroom learning, one program that can be applied is faststone. The purpose of study was to obtain overview effectiveness the implementation of online learning using faststone. The research subjects were students of class XI in financial accounting department totaling 69 students through data collection of observations, documentation, and giving questionnaires. Qualitative descriptive method was applied to analyze the collected data. Results showed that the application of learning model using faststone was more effective during online learning. Learning model used in this study can be applied by teachers to increase learning independence, interest and motivation, and courage to express ideas during online learning.